The Effect of the Availability of Infrastructure and Teachers’ Work Motivation on Teacher Professionalism - Asmawati Asmawati; Syaiful Eddy; Reva Maria Valianti (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of infrastructure facility availability and teacher work motivation on the professionalism of State Elementary School teachers in the Ikrar Cluster, Banyuasin III District, examining both partial and simultaneous effects. Employing a quantitative ex post facto method, data were collected via questionnaires and documentation from a sample of 138 teachers. Analysis was conducted using SPSS. The results confirm three key findings: (1) infrastructure availability has a significant positive influence on teacher professionalism; (2) teacher work motivation has a significant positive influence on professionalism; and (3) both factors together exert a statistically stronger combined influence. The novelty of this research lies in its empirical examination of the synergistic relationship between tangible resource allocation (infrastructure) and intangible human resource factors (motivation) within a specific Indonesian school cluster context. A central practical implication is that school district administrators must adopt integrated improvement policies that concurrently invest in physical facilities and foster motivational strategies to optimize teacher professionalism. The study contributes actionable empirical evidence to the field of educational management, demonstrating that teacher development is most effectively enhanced through a dual-focused strategy addressing both environmental and psychological supports.